IMPORTANCE OF BUSINESS SOLUTIONS BASED ON BLOCKCHAIN TECHNOLOGY - Marta Wiśniewska (Polityki Europejskie, Finanse i Marketing, 2020)
The aim of this study is to determine the essence of blockchain technology and its capabilities to be utilized in business operations. The paper discusses the importance of blockchain technology and practical possibilities of its application. Based on industry reports, statistics on investments of enterprises in blockchain technology and attitudes of their senior executives towards this technology, as well as the validity of its implementation, have been presented. In addition, the most important advantages of blockchain technology in relation to existing information technology (IT) systems have been specified. The article describes organizational barriers hindering investments in blockchain technology and its actual applications in companies. Performed analyses show that companies around the world are actively investing in blockchain technology. This technology has been found to be positively recognized in business by executives, however companies, while planning its implementation, face numerous barriers which mainly arise from a lack of legal regulations, and technical problems. On the other hand, blockchain technology can be used in many areas of company activities, especially in the supply chain.